Condiciones climáticas y perfiles electroforéticos bidimensionales del plasma seminal de toros Romosinuano - Herrera P., Natalia (2025)
The aim of this study was to determine the relationship between climatic conditions and the two-dimensional electrophoretic profiles (2D-PAGE) of seminal plasma from Romosinuano (RS) bulls raised in the Colombian Caribbean. Semen was collected from 10 RS bulls during the dry and rainy seasons and quality parameters such as sperm concentration, viability, rapid individual progressive movement (FIPM) and hypoosmotic swelling test (HOST) were evaluated. Seminal plasma proteins were separated by 2D-PAGE electrophoresis, and the relative amount of each spot was related to seminal quality. Seminal quality was higher in the dry season period where 117 spots were detected with molecular weights between 13 and 80 kDa and isoelectric points between 3.0 and 8.5. The relative amount of 26 and 30 spots showed a positive correlation with FIPM and HOST, respectively. The spots highly related to these parameters were predominantly found in the dry period. The differential expression of several proteins under the climatic conditions of the study could protect the spermatozoa of RS bulls against environmental changes to preserve and protect their reproductive functionality.